From crusade to hazard : the denazification of Bremen, Germany - Adams, Bianka J. (Bianka Janssen) (Scarecrow Press, Inc., 2009)
From Crusade to Hazard: The Denazification of Bremen Germany contributes to a better understanding of one of the most controversial and significant aspects of the U.S. occupation of Germany - the denazification program. It fills a significant scholarly void in an era when interest in military government and in methods of de-politicizing old classes of administrators affiliated with dictatorial regimes is being increasingly fueled by contemporary world events.